2016
DOI: 10.1155/2016/3608346
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium necrophorum Pharyngitis Complicated by Lemierre’s Syndrome

Abstract: We report the case of an 18-year-old woman who was referred to our outpatient clinic because of a 2-week history of sore throat, high fever, and neck tenderness unresponsive to a 7-day amoxicillin/clavulanic acid course. Infectious mononucleosis was initially suspected, but an extremely high value of procalcitonin and clinical deterioration suggested a bacterial sepsis, prompting the patient admission to our internal medicine ward. Blood cultures were positive for Fusobacterium necrophorum. CT scan detected a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In humans, Fusobacterium necrophorum can cause the rare and life-threatening Lemierre syndrome, which begins as bacterial pharyngitis and rapidly progresses to septic thrombophlebitis of the jugular vein (3). Lemierre syndrome most frequently manifests in patients age 15 to 30 and can lead to further complications, including pharyngeal and lung abscesses (4). F.…”
Section: Announcementmentioning
confidence: 99%
“…In humans, Fusobacterium necrophorum can cause the rare and life-threatening Lemierre syndrome, which begins as bacterial pharyngitis and rapidly progresses to septic thrombophlebitis of the jugular vein (3). Lemierre syndrome most frequently manifests in patients age 15 to 30 and can lead to further complications, including pharyngeal and lung abscesses (4). F.…”
Section: Announcementmentioning
confidence: 99%
“…A study by Leli et al showed that F. nucleatum bloodstream infections correlated to a median procalcitonin level of about 0.38 ng/mL [ 17 ]. One case report described a procalcitonin level elevated to 294 ng/mL in a patient with F. necrophorum pharyngotonsillitis, Lemierre’s syndrome, and bacteremia [ 18 ]. This case report describes a rare case of extreme procalcitonin elevation to over 200 ng/mL in the setting of F. nucleatum liver abscess and bacteremia.…”
Section: Discussionmentioning
confidence: 99%
“…We found that 9 out of 16 patients did see a healthcare provider (56%) with one of them having been previously hospitalized before being transferred to another facility. and 9 of those 10 patients received antibiotics (56%) [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] .…”
Section: Discussionmentioning
confidence: 99%
“… Author (year) Assessed as outpatient Outpatient antibiotics prescribed? Initial symptoms Tawa et al (2016) [3] Yes None odynophagia, left cervical pain, and fever Stefan et al (2016) [4] Yes Clarithromycin 1-week history of severe sore throat and fever Roland et al (2016) [5] Yes Amoxicillin/clavulanic acid dental infection present in the left inferior premolar for a month Chamseddin et al (2016) [6] Yes Amoxicillin severe odynophagia and sore throat Fielding et al (2016) [7] Yes Clarithromycin 7-day history of worsening dysphagia, non-productive cough, hoarseness, fever, rigors, general malaise and anorexia Panchavati et al (2017) [8] Yes Ampicillin/sulbactam and amoxicillin fever, rigors and sore throat 7 days Faraone et al (2016) [9] Yes Amoxicillin/clavulanic acid 2-week history of sore throat, high fever, and mild neck tenderness Kumral et al (2017) [10] No None 7 day history of fever (Tmax 40.4C), left sided throat pain, fatigue, and myalgias Budhram et al (2017) [11] No None 1 week of right sided partial ophthalmoplegia and ptosis 4 month history of headache Farhan et al (2016) [12] ...…”
Section: Discussionmentioning
confidence: 99%